The 6-GHz methanol multibeam maser catalogue – V. Galactic longitudes 20°–60 - Breen, S. L.; Fuller, G. A.; Caswell, J. L.; Green, J. A.; Avison, A.; Ellingsen, S. P.; Gray, M. D.; Pestalozzi, M.; Quinn, L. J.; Richards, A. M. S.; Thompson, M. A.; Voronkov, M. A. (Monthly notices of the Royal Astronomical Society, 2015)
We present the fifth portion of an unbiased survey of the Galactic plane, |b| ≤ 2°, for 6668-MHz methanol masers. This section of the survey completes the Galactic longitude range visible to the Parkes radio telescope, incorporating the longitude range 20°–60°. Within this section of the survey we find 265 methanol masers, 64 new to the survey, bringing the total number of methanol masers detected across the full longitude coverage (186°, through 0°, to 60°) to 972 sources.